Antidiabetic, anti-inflammatory and cytotoxic potential of Theobroma cacao Linn. husk aqueous extracts - Julius Kevin Cura (SpringerOpen, 2021)
Abstract Background Theobroma cacao Linn. husks are considered agricultural wastes, but studies show that they exhibit natural compounds that may be used in alternative medicine. Hence, this study was conducted to determine the antidiabetic, anti-inflammatory, and cytotoxic potential of T. cacao husk aqueous extracts (TCE). Results A significantly higher glucose dialysis retardation index (GDRI) was shown by 10% TCE than the rest of the concentrations (1%, 3%, 5%, 7%) (P<0.05), and its activity is comparable with 5% Metformin (positive control) after 30 min, 60 min, 120 min and 180 min of incubation. The 7% TCE also showed significantly higher GDRI than the 5%, 3%, and 1% concentrations (P<0.05), and its activity is comparable with 5% Metformin after 60 min and 180 min of incubation. Moreover, 10% TCE exhibited a significantly higher glucose uptake percentage than the rest of the samples (P<0.05) and has activity comparable with 5% Metformin. The anti-inflammatory assay showed a significantly higher inhibition rate of 10% TCE than the rest of the concentrations (P<0.05), and its activity is comparable with 5% Diclofenac (positive control). The cytotoxicity assay showed that the percentage mortality of brine shrimps after 24 h of exposure to the different TCE samples is less than 50%. Conclusion This study concludes that T. cacao husk aqueous extract has potential antidiabetic and anti-inflammatory properties without being toxic to cells.